The effect of sleepiness in situation awareness: A scoping review. - Silva Gomes, Virgınia; Cardoso Júnior, Moacyr Machado (Work, 2024)
BACKGROUND: Situational awareness is the acquisition of information from elements present in the work environment, the perception of the meaning of this information, and the prediction of future working conditions. Sleepiness and fatigue can influence an individual's ability to reach situation awareness, decision-making, and performance on a task. OBJECTIVE: This scoping review examines methods used to assess situational awareness, fatigue, sleepiness, and their interrelationships. METHODS: A systematic search of online databases was conducted to identify experimental, peer-reviewed articles published in English between 2017 and 2022. A total of 29 publications were selected for analysis. RESULTS: The selected studies originated from various countries, primarily in the northern hemisphere. Health and automotive engineering were the academic categories with the highest publications. The studies employed objective and subjective methods to assess situational awareness, fatigue, and sleepiness. CONCLUSIONS: Most studies reported a decline in situational awareness during fatigue and sleepiness conditions, although one study did not find this association. Future research should focus on employing objective methods to analyze cognitive factors, increasing sample sizes, and conducting testing in real-world situations.